Views of German mental health professionals on the use of digital mental health interventions for eating disorders: a qualitative interview study - Mayer, Gwendolyn; Lemmer, Diana; Michelsen, Ina; Schrader, Pauline; Friederich, Hans-Christoph; Bauer, Stephanie (Journal of eating disorders, 2024)
IntroductionDigital mental health interventions (DMHIs) are getting increasingly important for mental health care. In the case of eating disorders (EDs), DMHIs are still in early stages. Few studies so far investigated the views of mental health professionals for EDs on the integration of DMHIs in routine care.ObjectiveTo gain insights into the experiences, perspectives, and expectations of mental health professionals for EDs regarding DMHIs and to identify requirements for the future integration of DMHIs into routine care.MethodsSemi-structured qualitative telephone interviews with 24 German mental health professionals treating patients with EDs were conducted. A content analysis following a deductive-inductive approach asked for experiences, advantages and chances, disadvantages and boundaries, desired functions and properties, target groups, and general conditions and requirements for DMHIs for patients with EDs.ResultsOnly few professionals reported experiences with DMHIs besides video-based psychotherapy during the pandemic. From the therapists' point of view, DMHIs have the potential to deliver low-threshold access for patients with EDs. Useful functionalities were seen in digital meal records, skills training, and psychoeducation. However, a stable therapeutic alliance was reported as an important prerequisite for the successful integration into care. Therapists expressed concerns in case of severe anorexia nervosa or suicidality. The participants felt to be informed inadequately on recent developments and on the evidence base of DMHIs.ConclusionsMental health professionals for EDs show positive attitudes towards DMHIs, however many barriers to the integration in routine care were observed. The highest potential was seen for the use of DMHIs in addition to outpatient care and in aftercare. Specific requirements for DMHIs are related to different areas of the healthcare spectrum and for the different symptom profiles in anorexia nervosa, bulimia nervosa and binge eating disorder. Targeted DMHIs are needed and appropriate especially for concepts of blended care. Digital mental health interventions are therapeutic services for people with a mental disorder that can be delivered on electronic devices. They are getting increasingly important, as many patients have to wait long for a therapy. In eating disorders these interventions are still in early stages. Twenty-four telephone interviews were held with German professionals treating adolescent and adult patients with eating disorders. The aim was to understand their experiences, perspectives, and expectations regarding digital mental health interventions and to find out what is needed to integrate them into care in the future. In general, the interview partners showed positive attitudes towards these interventions. However, only few reported experiences and many obstacles were observed. The highest potential was seen for the use in addition to care outside the hospital setting and after treatment has ended. However, in case of a severe eating disorder, such as anorexia, or self-harm and suicidality, they were against the use of digital interventions. A stable personal relationship to their patients was seen as particularly important before recommending a digital intervention. Finally, the interview partners felt not informed in a sufficient way on the scientific basis and regulations regarding digital mental health interventions.
Gesehen am 27.06.2024